Information Systems for Crisis Response and Management in Mediterranean Countries : second international conference, ISCRAM-med 2015, Tunis, Tunisia, October 28-30, 2015, proceedings /: second international conference, ISCRAM-med 2015, Tunis, Tunisia, October 28-30, 2015, proceedings. (2015) - Unknown
No abstract available